How could the ethnic conflicts take place in Bohemia in the second half of the 19th century? (Theatrum historiae, 2011)
This article attempts to outline three areas within which ethnic conflict was stirred up in Bohemia in the second half of the 19th century and accelerated the formation of a strong national identity. The liberalisation in Bohemia inhabited by two nations brought about thousands of such conflict situations for all social layers alike; however, only three were of crucial importance: the struggle for parliamentary mandates and seats in municipal governments, the struggle for the official language and the language of instruction and, last but not least, the struggle for pupils and students. As is widely known, conflicts where the opponent is easy to pinpoint can serve as the best catalyst for the formation of a strongly instrumental identity.